1999
DOI: 10.1557/proc-605-247
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Properties for Micro-Sized Ni-P Amorphous Alloy Specimens

Abstract: Fatigue crack propagation tests at different stress ratios of 0.1 and 0.5 have been performed on microsized Ni-P amorphous alloy specimens to investigate the influence of stress ratio in the crack growth properties of microsized materials. The specimens tested were cantileverbeam-type with dimensions of 10 × 12 × 50 νm3 prepared by focused ion beam machining. Notches with a depth of 3 [m were introduced in all specimens. The entire set of fatigue tests as performed using a newly developed fatigue testing machi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Fatigue tests were carried out at a frequency of 10 Hz, using a constant load amplitude (Δ P /2, where Δ P = P max − P min ) of 2 mN and stress ratios, R (where R is given by minimum load ( P min )/ maximum load ( P max ) applied over the fatigue cycle), of 0.1, 0.3 and 0.5, respectively. This fatigue test condition was determined from previous research 21 . Although the crack length was not directly measured in this machine, the change in specimen compliance was monitored during testing.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Fatigue tests were carried out at a frequency of 10 Hz, using a constant load amplitude (Δ P /2, where Δ P = P max − P min ) of 2 mN and stress ratios, R (where R is given by minimum load ( P min )/ maximum load ( P max ) applied over the fatigue cycle), of 0.1, 0.3 and 0.5, respectively. This fatigue test condition was determined from previous research 21 . Although the crack length was not directly measured in this machine, the change in specimen compliance was monitored during testing.…”
Section: Methodsmentioning
confidence: 99%
“…This fatigue test condition was determined from previous research. 21 Although the crack length was not directly measured in this machine, the change in specimen compliance was monitored during testing. Crack initiation was, therefore, determined by monitoring the specimen compliance.…”
Section: Fatigue Testingmentioning
confidence: 99%
See 2 more Smart Citations
“…The recent development of bulk metallic glasses (BMGs) and amorphous-nanocrystalline composites has renewed interest in their potential as structural materials [1,3]. It has been confirmed that some metallic glasses have a unique combination of various properties and are suitable for many applications [4]. However, mechanical behavior and prediction of failure in BMGs at temperatures below the glass transition temperature Tg are still under active investigations.…”
Section: Introductionmentioning
confidence: 99%